Information Diffusion Management and Knowledge Sharing 2020
DOI: 10.4018/978-1-7998-0417-8.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing between Enterprises of the Same Group

Abstract: This exploratory study seeks to promote investigation about knowledge sharing between enterprises of the same enterprise group and is motivated by the growing importance of knowledge management (KM) to businesses. The data was collected from Community Innovation Survey (CIS) 2012 and three linear regressions were performed (one to all enterprises, one to SME and one to large enterprises). The results show that cooperation for product or process innovation and service innovation influence knowledge sharing betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Knowledge application can help to transform knowledge from being a potential power tool into actual innovations or inventions, which can enhance overall performance of organizations (Matin et al, 2013). Knowledge use is basically important to knowledge recipient who employ knowledge for innovation and consequently improves organizational performance (Carvalho & Gomes, 2017). Gottschalk (2007) also emphasizes the necessity of using knowledge in organizational practices, processes and policies.…”
Section: Knowledge Applicationmentioning
confidence: 99%
“…Knowledge application can help to transform knowledge from being a potential power tool into actual innovations or inventions, which can enhance overall performance of organizations (Matin et al, 2013). Knowledge use is basically important to knowledge recipient who employ knowledge for innovation and consequently improves organizational performance (Carvalho & Gomes, 2017). Gottschalk (2007) also emphasizes the necessity of using knowledge in organizational practices, processes and policies.…”
Section: Knowledge Applicationmentioning
confidence: 99%
“…Firms that are part of an enterprise group are well informed about the capabilities and potential of the individual partners owing to knowledge and resource pooling of other members of their group (Saridakis et al, 2019). A study conducted by Carvalho and Gomes (2020) found that firms' collaborations for innovation (product, process and service) influence knowledge dissemination between enterprises that belong to the same enterprise group, and this contributes to learning organizations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hence, The Stakeholder theory could support managers to understanding about the moral and value for managing the firms with well ethics in business within shareholders and many groups. (Hooks and Stewart, 2015, Ren et al, 2016, Hernández-Perlines, 2016, Carvalho and Gomes, 2017, Forthofer et al, 2016 The The digital transformations within firms and the digital marketing.…”
Section: Proposed the Framework And Hypothesis Developmentmentioning
confidence: 99%